Data complexity and computer assisted chronology: Methods and discoveries. - Falk, David A. (Archaeometry)
Data complexity is one of the most formidable problems facing modern chronology. Chronologists in the past have attempted to mitigate the problem through reducing the amount of math needed by curating the data set. However, evaluating the significance of curated data can be subjective and often incorrect because choosing the most significant synchronisms is not always intuitive. For better chronologies, new methods and tools are needed that retain complexity and interdependence with cross‐cultural data but eliminate the subjectivity of human data curation. The consequence of these needs would be that constructing a chronology requires not just hundreds of thousands of calculations but also an additional number of calculations to show that a chronology is potentially valid. This paper posits that one can craft better, more accurate historical chronologies using a tool such as the Groundhog Chronological Laboratory, which was specifically designed for that purpose. Groundhog is uniquely designed to help historians and chronologists design new chronologies and test them for internal consistency.